Tayub as a Symbolic Interaction Medium in Sedekah Bumi Ritual in Pati Regency - Suryani, Sisca Dwi (Harmonia: Journal of Arts Research and Education, 2014)
This study aims to find, understand, and describe the process of symbolic interaction in sedekah bumi ritual and the supporting symbols of Tayub as the symbolic interaction medium in the ritual. This study applies qualitative methods with the holistic approach. The research was conducted in Dukuh Guyangan, Desa Sidoluhur, Kecamatan Jaken, Kabupaten Pati. In collecting the data, observation, interview, and documentation technique were implemented. Further, the data were analyzed using the technique of data reduction, data presentation, drawing conclusion, as well as verification. The data was validated using the sources triangulation, the technique triangulation, and the time triangulation. Tayub as the medium of symbolic interaction realizes in four interaction processes, as follows: 1) symbolic interaction processes between the ritual actors and the spirits of ancestors reflected in kenduren procession held in punden, 2) symbolic interaction process between ledhek and pengibing that is embodied in ibingan, 3) symbolic interaction process between wiraswara and the audiences that is seen during the dance performance, 4) symbolic interaction process between pengrawit and ledhek that is reflected in the dance movements and the accompanying music. The meanings of symbol behind the ritual itself are reflected through the realization of symbolic interaction. It consists of three elements, as follows: 1) kenduren prayer, 2) offerings and ambeng, 3) Tayub dance.